O balanced scorecard como ferramenta de gestão no Instituto Federal de Santa Catarina - Mendes, Oizes Vieira (2019)
Public Education Institutions do not base their success on their ability to make a profit, but on the social impact generated. This legitimizing support is consolidated through a communication that can convey the importance of education for the citizen. In this context, the Balanced Scorecard (BSC) is a tool that can make tangible how the application of resources in the institution generate value to society. This study aims to propose improvement actions to the BSC model used by the IFSC. Thus, the research addresses the problem qualitatively, exploratory and descriptive in nature. The structural consolidation of the research was through a case study that used as data collection document analysis, focal interviews and participant observation. The results reinforce the importance of measuring strategic indicators for decision making, as they provide the manager with the perception of the reality that surrounds him and which strategies are necessary for the fulfillment of the mission and the realization of the institutional vision. Another relevant point is the difficulty in disseminating BSC without the use of a system that facilitates managers' access to strategic information. Finally, it was found that the BSC acts fully in directing actions on campuses. It is concluded that there is still a need for further consolidation of the institution's governance process so that BSC implementation can be implemented. This process involves designating a strategic objectives officer who sets guidelines for Campi actions. This strengthens strategic alignment across the institution.